Pemanenan Air Hujan untuk Meningkatkan Aksesibilitas Air di Permukiman Pesisir, Kasus Jakarta, Indonesia - Analissa Huwaina; Hayati Sari Hasibuan; Endrawati Fatimah (Department of Urban and Regional Planning, Diponegoro University, 2022)
Water is a basic need for human activities, especially for daily needs. Currently, there are still households on the coast of North Jakarta that rely on non-piped water as a source of clean water; even households with toddlers rely on unfit water sources due to economic conditions. It is difficult to access clean and expensive water, so they use groundwater, which is detrimental to the environment and causes land subsidence, or buys expensive and unaffordable water. Coupled with poor environmental sanitation conditions come from shellfish waste and household waste. Rainwater harvesting can be a solution for fisher’s settlements as a clean water source. This study aims to increase water accessibility in coastal settlements with the potential that exists in the surrounding environment. The study used a direct survey and experiment on RWH (Rainwater Harvesting) with a survey sample of 266 respondents. The results show that most coastal communities rely on more than one water source. After direct experimentation, the community accepts rainwater as an alternative to clean water, reducing the cost of public spending for clean water. Tests on reliable water quality and rainwater from rainwater harvesting systems showed that E.Coli still contained. Water quality and distribution are influenced by many factors, such as politics and applicable government regulations. Further research is needed on other water supply methods in coastal settlements.